2005
DOI: 10.1089/aid.2005.21.145
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Full-Length Human Immunodeficiency Virus Type 1 Genome Reveals a Variable Spectrum of Subtypes B and F Recombinants in São Paulo, Brazil

Abstract: Recombination is one of the major mechanisms contributing to human immunodeficiency virus type 1 (HIV-1) variability. Analysis of pol gene sequences of 215 HIV-1 samples from São Paulo, Brazil classified 189 sequences as subtype B (87.9%), 8 sequences as subtype F (3.7%), and 18 sequences (8.4%) as B/F recombinants. After the analysis of the pol gene, a subset of six recombinant samples composed of sequences with a related recombinant pol structure was selected for full-length genome analysis to identify a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
47
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 21 publications
7
47
2
Order By: Relevance
“…In Brazil, subtypes B, C, F, and recombinants cocirculate. In Sao Paulo, subtype B accounts for 90% of the infections, and subtype F for 4% [20]. B/F recombinants, some of which share common breakpoints in the pol gene but differ in their structure in other genes, were also found, in concordance with previous studies that found several B/ F URFs but failed to detect a CRF in Brazil.…”
Section: South America and The Caribbeansupporting
confidence: 89%
“…In Brazil, subtypes B, C, F, and recombinants cocirculate. In Sao Paulo, subtype B accounts for 90% of the infections, and subtype F for 4% [20]. B/F recombinants, some of which share common breakpoints in the pol gene but differ in their structure in other genes, were also found, in concordance with previous studies that found several B/ F URFs but failed to detect a CRF in Brazil.…”
Section: South America and The Caribbeansupporting
confidence: 89%
“…Recombination breakpoints have been found in nucleotide region 230-330, i.e., in the sequence that folds to the predicted structure, between the pol gene sequences from different subtypes, such as between subtypes A and B, A and D, and B and D, as well as between B and F (Quarleri et al 2004;Yang et al 2004;Sa Filho et al 2005). However, the existence of breakpoints in this region is insufficient to define a recombination hot spot.…”
Section: Role Of the Rna Secondary Structurementioning
confidence: 99%
“…Studies on the env and pol regions indicate co-circulation of subtypes B (62.5-82.9%), F (8-18%) and C (3-45%) (Bongertz et al, 2000;Brindeiro et al, 2003). Evidence of B/F and B/C recombinants involving the env, gag, nef and pol regions have been reported in southeast Brazil (Guimaraes et al, 2002;Sa Filho et al, 2005;Sanabani et al, 2006). There are regional differences in the pattern of HIV-1 subtypes.…”
Section: Introductionmentioning
confidence: 99%